Simulação do escoamento superficial na bacia experimental de Santana do Ipanema - Rocha, Sergio Renato Ávila Glasherster da (2008)
The semiarid region of Alagoas, that occupies 45,6% of State, presents an irregular distribution of rain, shallow soils and high evaporation taxes, being necessary to know with more accuracy the hydrological processes and the relations between them to improved the water resources management of the region. The aim of this study was to simulate surface runoff for different land occupation and use scenarios in the Experimental Basin of Santana do Ipanema (BESI), located in the Gravata Creek Watershed (BHRG). For this reason, the BESI was deployed, composed by three units of study: two subbasins of 3,35 and 0,09 km2, and a microbasin of 5.000 m2. It was applied the runoff and erosion model Kineros2 for nine rain events occurred during 2007 and 2008 in the BHRG and in the largest sub-basin in the BESI. In the current scenario of land occupation and use, the runoff coefficient value ranged from 0,02 to 0,55 for the BHRG, with an average of 0,27, while for the sub-basin of the BESI the range of variation was from 0,05 to 0,69, with average value of 0,25. It was found that the parameters of largest sensibility are: mean capillarity degree (G), saturated hydraulic conductivity (Ks) and Manning s coefficient (n). The average value of runoff coefficient for the studied events ranged around 40%, when the initial condition of soil humidity was modified between 10% and 90%, for both basins. In land occupation and use scenarios analysis, for the BHRG, a total deforestation condition had a average runoff coefficient of 0,59 while for a caatinga condition the value was 0,08. In the BESI, the runoff coefficient was 0,64 and 0,14, respectively, for the same conditions. From the analysis of these values, was concluded that in two studied basins the effect of land deforestation leads to a considerable increase in runoff volume, contributing further to water scarcity in the region.